Why the Humanities Are Necessary to Public Policy, and How - Bartel, Anna (Maine Policy Review, 2015)
To ask what this issue of Maine Policy Review asks is to assume that the humanities are valuable and/or useful, both in general and in particular to public policy. So we should be asking not only how policy can help the humanities but how the humanities can help policy. Anna S. Bartel sees several answers and tries to map them by exploring intersections of humanities and public policy and by asking what public policy needs that the humanities can contribute. Four stages of policy can all benefit from humanistic education, programming, and dispositions: conceptualization, crafting, implementation, and evaluation